2021
DOI: 10.1093/bib/bbab261
|View full text |Cite
|
Sign up to set email alerts
|

TransRef enables accurate transcriptome assembly by redefining accurate neo-splicing graphs

Abstract: RNA-seq technology is widely employed in various research areas related to transcriptome analyses, and the identification of all the expressed transcripts from short sequencing reads presents a considerable computational challenge. In this study, we introduce TransRef, a new computational algorithm for accurate transcriptome assembly by redefining a novel graph model, the neo-splicing graph, and then iteratively applying a constrained dynamic programming to reconstruct all the expressed transcripts for each gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Moreover, each labeled paired path corresponds to a segment of an expressed transcript and should be covered by at least one predicted transcript. To achieve this goal, we strategically use the label information and the reliable labeled paired paths in the labeled splice graph and employ a new labeled-based dynamic programming algorithm that is similar to our previous study ( Yu et al., 2021 ) to generate the transcript-representing path cover over each labeled graph. In detail, we recover the expressed transcripts by the following steps.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, each labeled paired path corresponds to a segment of an expressed transcript and should be covered by at least one predicted transcript. To achieve this goal, we strategically use the label information and the reliable labeled paired paths in the labeled splice graph and employ a new labeled-based dynamic programming algorithm that is similar to our previous study ( Yu et al., 2021 ) to generate the transcript-representing path cover over each labeled graph. In detail, we recover the expressed transcripts by the following steps.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, we found TaTKW-1A, which has two major candidate genes, TraesCS1A02G045300 and TraesCS1A02G058400, with grainrelated traits (Figure 7). We identified them in the transcriptome of wheat grain through the website https://www.ebi.ac.uk/gxa/home (Gillies et al, 2012;Li et al, 2013;Takafuji et al, 2021;Yu et al, 2021) (Figure S5). Results showed that both genes were expressed during grain development, although the expression profiles of these two genes clearly differ during grain development; both of them were expressed in the pericarp, endosperm, and seed coat (Li et al, 2013;Yu et al, 2021).…”
Section: Tatkw-1amentioning
confidence: 99%
“…We identified them in the transcriptome of wheat grain through the website https://www.ebi.ac.uk/gxa/home (Gillies et al, 2012;Li et al, 2013;Takafuji et al, 2021;Yu et al, 2021) (Figure S5). Results showed that both genes were expressed during grain development, although the expression profiles of these two genes clearly differ during grain development; both of them were expressed in the pericarp, endosperm, and seed coat (Li et al, 2013;Yu et al, 2021). Specifically, TraesCS1A02G045300 is important because it was expressed consistently from anthesis to maturity (Pfeifer et al, 2014;Pearce et al, 2015;Yu et al, 2021).…”
Section: Tatkw-1amentioning
confidence: 99%